Lifelong Islamic education: positive youth development through Ulul Albab Tahfiz model - Ahmad, Zaidah Nor; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Mohd Fakhruddin, Fathiyah (Human Resource Management Academic Research Society, 2020)
Education is one of the social challenges faced by youths in Malaysia. According to the Malaysian Youth Policy, (2015), youths aged 15 to 18 years are categorized as early youth. They are under school youth category and education are emphasized on them. The education ecosystem is very important as a basis for the formation of a developed country. Continuous education as Lifelong Islamic Education (LIE) applied in the implementation of Ulul Albab Tahfiz Model (UATM) is seen as one of the important elements in education that can lead to positive youth development (PYD). Thus, using the qualitative case study methodology, this paper exploring on how LIE that takes place in the UATM can attain PYD. Data are obtained through analysis documents and semi-structured interview involving 8 students, 2 teachers and 2 guardians. The findings of the study found that the implementation of LIE able to develop individual assets and ecological assets in youth and lead to PYD. In conclusion, the implementation of UATM has a potential to develop PYD and subsequently strive to be one of the initial efforts to highlight the potential in the youth rather than the deficit approach aimed at addressing the social problems of youth.